Narcolepsy in the light of modern diagnostic, clinical and therapeutic concepts - Kowalski, Adrian; Kowalska, Iwona; Kowalska, Magdalena; Dróżdż, Wiktor; Nowaczyk, Alicja (Journal of Education, Health and Sport, 2018)
Narcolepsy is a chronic neurological disease classified as hypersomnia of central origin. Core symptoms of the disease (hypersomnia and cataplexy) are particularly burdensome for patients. The etiology of the disease is not fully understood. There are several theories explaining the essence of the disease. One of the possible causes is the disruption of the autoimmune system leading to the disappearance of hypocretin-releasing neurons. Currently, multicenter studies on synthesizing hypocretin-like proteins that may be the basis of causal narcolepsy treatment are conducted. As yet pharmacotherapy contributes only to reduce the symptoms of the disease. Commonly used medications are amphetamine derivatives, modafinil, pitolisant and γ-hydroxybutyric acid sodium salt (GHB).